We Dissent : Talking Back to the Rehnquist Court, Eight Cases That Subverted Civil Liberties and Civil Rights. - Avery, Michael (NYU Press, 2009)
The lawyers and legal commentators who contribute to We Dissent unanimously agree that during Chief Justice William Rehnquist's nineteen-year tenure, the Supreme Court failed to adequately protect civil liberties and civil rights. This is evident in majority opinions written for numerous cases heard by the Rehnquist Court, and eight of those cases are re-examined here, with contributors offering dissents to the Court's decisions. The Supreme Court opinions criticized in We Dissent suggest that the Rehnquist Court placed the interests of government above the people, and as the dissents in this.